Efficacy of Regional Blocks or Local Anaesthetic Infiltration for Analgesia After Caesarean Delivery: A Network Meta-Analysis of Randomized Controlled Trials. Issue 4 (21st December 2022) - Singh, N.P.; Monks, D.; Makkar, J.K.; Palanisamy, A.; Sultan, P.; Singh, P.M.
Abstract : ( Anaesthesia . 2022;77:463–474. doi: 10.1111/anae.15645) With cesarean delivery (CD) rates on the rise globally, it is important to understand the most effective methods of managing postoperative pain, which can be moderate to severe. Effective analgesia following CS has the long-term benefits such as decreasing opioid consumption, postpartum depression, and the likelihood of chronic pain. While long-acting neuraxial opioids reduce opioid requirements, breakthrough pain is not uncommon and neuraxial interventions may be contraindicated for some women. Local anesthetic infiltration has been increasingly used to reduce pain without significant adverse effects and may add the benefit of visceral analgesia. With many approach sites for treatment (direct wound infiltration, ilio-inguinal nerve, transversus abdominis plane, erector spinae plane, transverse fascia plane, and quadratus lumborum plane), it has not yet been studied if certain sites offer greater benefit over others. This network meta-analysis compares and ranks injection sites for efficacy of pain relief following CD.